Homotopy Perturbation Method for Semi-Bounded Solution of the System of Cauchy-Type Singular Integral Equations of the First Kind - Husnida Mamatova; Zainidin Eshkuvatov; Shahrina Ismail (Semarak Ilmu Publishing, 2025)
Indexed by MyCite